Problematika "cordevolskih" apnencev in dolomitov v slovenskih Južnih Alpah - Celarc, Bogomir (Geologija, 2004)
Stratigraphic position and age of the so called Cordevolian limestone and dolomite in the Slovenian part of the Southern Alps is a long lasting problem.Its name originates from the (somewhere abandoned) Cordevolian substage (Lower Carnian). Limestone and dolomite both correspond to the Cassian dolomite from the Italian Southern Alps. Platform type of limestone and dolomite, which could be genetic and time equivalent with the Ladinian Schlern (Scilliar) dolomite, is unknown in Slovenia. In the NE part of the Kamnik-Savinja Alps, the Korošica formation (Upper Ladinian) overlies platformlimestone and dolomite of the Ojstrica Formation (Ladinian). Diploporaannulata is also present in the Ojstrica formation. Various Ladinian rocks in the Julian Alps and Southern Karavanke are mainly of the Lover Ladinian age, whereas the overlying massive limestone and dolomite ("Cordevolian limestone and dolomite") are partially of the Ladinian and partially of the Carnian age. There are no Upper Ladinian "Wengen" beds in thecarbonate massive, so it is impossible to draw a time line between the Ladinian and the Carnian stages. We can therefore conclude, that litological boundaries do not coincide with the chronostratigraphic ones.
Keywords: apnenec; dolomit; Kamnik–Savinja Alps; Kamniško-Savinjske Alpe; karbonatne kamnine; Slovenia; Slovenija; stratigrafija; stratigraphy; trias